Nâng cao khả năng nhuộm của sợi tre bằng phương pháp xử lý plasma không khí ở áp suất thường - Hoà, Tạ Thị Phương; Dương, Lê Đại; Oanh, Đoàn Thị Yến; Khanh, Vũ Thị Hồng; Trang, Hứa Thuỳ (Vietnam Journal of Chemistry, 2012)
Atmosphere pressure air plasma was used for surface treatment of technical and textile bamboo fibers. The changes of the percent weight loss, surface morphology, dynamic contact angles, dry tensile strength as well as the dyeing rate of bamboo fibers were investigated. The measurement results as well as the SEM and AFM images show that plasma treatment caused the eatching the surface, leading to cleaner and rougher surface, lower contact angle to water of the bamboo fibers, which enable a better wettability and adhesion of dye onto fiber surface. Plasma treated fibers possessed higher dyeing rate to the dyes Direct Sky Blue 5B and Direct Red Rose. In addition, the dry tensile strength of textile bamboo fiber increased about 10% at the textile fiber after plasma treatment.